Contextualization of The Talkin Hadith in The Book Tarjamah Bulugul Maram by Ahmad Hassan - Akbar, Riko; Muhid, Muhid; Nurita, Andris; Muthaharoh, Isnaini Lu'Lu' Atim (AJIS: Academic Journal of Islamic Studies, 2024)
This research examines Ahmad Hassan's thoughts regarding Ahmad Hasan's thoughts on the Talkin hadith in the book Tarjamah Bulugh al-Maram. This research uses a qualitative approach. In data mining, library research is used by searching various written sources to obtain other supporting data. Data analysis in this research uses the content analysis method by discussing in depth the information content of the collected data in accordance with the research objectives and problems. The theory used is Syuhudi Ismail's contextualization theory. The results of this research are that Ahmad Hassan interprets what is meant by talkin as teaching, meaning teaching the deceased to answer the questions given by the Angels Munkar and Nakir in the grave regarding I'tikad. which must be believed while living in the world. For Ahmad Hassan, talkin is invalid and not justified because there is no explanation in the Quran and hadith.